A comprehensive review on plant‐based natural fiber reinforced polymer composites: Fabrication, properties, and applications. Issue 5 (17th February 2023) - Akhil, U. V.; Radhika, N.; Saleh, Bassiouny; Aravind Krishna, S.; Noble, Niveditha; Rajeshkumar, L.
Abstract: Natural fiber‐reinforced polymer composites (NFPCs) have gained limelight in many applications during the recent years, owing to their availability, as well as superior mechanical characteristics, cost‐effectiveness, biodegradability, and lightweight. A comprehensive understanding of the manufacturing methods, proeprties and characteristics of natural fibers pave way for begetting a wide spectrum of applications for the NFPCs in automobile, aerospace, electronics, and other engineering fields. The current review article is about natural fiber‐reinforced composites, the commonly used fabrication methods, including fiber pre‐treatments, and numerous intermediate steps added to achieve improved bonding, processability of these composites, their properties and application prospects. Various state‐of‐the‐art methods like additive manufacturing, vaccum bag molding, and autoclave has also been discussed. The mechanical properties obtained through various fiber reinforcements in accordance with process parameters has a substantial impact in the industrial applications of NFPCs. The tribological applications of NFPCs are becoming increasingly important in order to deal with the mechanical and chemical wear and tear during their service life in contact applications. Flammability behavior and biodegradability assessment of NFPCs are important for high‐temperature and outdoor environmental applications of these materials. The review also includes a comprehensive discussion about the trending applications and future prospects for NFPCs. Abstract :